2007
DOI: 10.1093/brain/awm263
|View full text |Cite
|
Sign up to set email alerts
|

Serum GFAP is a diagnostic marker for glioblastoma multiforme

Abstract: A serum marker for malignant cerebral astrocytomas could improve both differential diagnosis and clinical management of brain tumour patients. To evaluate whether the serum concentration of glial fibrillary acidic protein (GFAP) may indicate glioblastoma multiforme (GBM) in patients with single supratentorial space-occupying lesions, we prospectively examined 50 consecutive patients with histologically proven GBM, World Health Organization (WHO) grade IV, 14 patients with anaplastic astrocytoma (WHO grade III)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
183
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(199 citation statements)
references
References 35 publications
13
183
0
3
Order By: Relevance
“…Increased plasma GFAP concentrations were found in patients with malignant gliomas and traumatic brain injury (36,37 ). Due to the hemispheric stroke-specific inclusion criteria (i.e., presence of both hemiparesis and at least 1 sign of hemispheric involvement), a low number of patients with stroke mimic were enrolled in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Increased plasma GFAP concentrations were found in patients with malignant gliomas and traumatic brain injury (36,37 ). Due to the hemispheric stroke-specific inclusion criteria (i.e., presence of both hemiparesis and at least 1 sign of hemispheric involvement), a low number of patients with stroke mimic were enrolled in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the astrocytic properties of astrocytomas, vimentin is often referred as a marker for these brain tumors [51] , and it was described that its co-expression with nestin may serve as an indicator of an astrocytoma with an enhanced motility and invasive potential [52] . Mature astrocytic markers, such as GFAP, are also described to be expressed in glioma cells [53][54][55] , although Jan et al [51] showed that the malignant progression to a higher degree of invasiveness is associated with an increase in vimentin expression and a progressive loss of GFAP. Besides the expression of immature and astrocytic cell markers, gliomas also express neuronal proteins such as β-III-tubulin [56,57] and MAP2 [58] , both indicators of a high-grade astrocytoma [58] .…”
Section: Discussionmentioning
confidence: 99%
“…певтическими дозами в эксперименте исследовате-ли уже применяли, в частности, радиоактивные маркеры [23], МРТ-мониторирование [24], методы иммуногистохимии [25], позитронно-эмиссионную томографию, количественный анализ альбумина [26] и др. Аналогичные исследования в единичных случаях уже проводятся на пациентах.…”
Section: Discussionunclassified